PENGARUH BIMBINGAN KELOMPOK TERHADAP TINGKAT PROKRASTINASI AKADEMIK SISWA DI SMPN 14 PEKANBARU TP.2016/2017 - Sinarwati '; Tri Umari; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objectives of this research are 1) To know the description of academic procrastination level of students before and after the implementation of group guidance, 2) to know the difference of academic procastiasi level before and after group guidance in the experimental group, 3) to know the difference of academic procrastination level of pre test students with post test at Control group, 4) to know the difference of academic procrastination level of the students in the post test of the experimental group and post test of the control group, 5) to know the influence of group guidance on the level of academic procrastination of the learners. Data collection tool in the form of an academic procrastination questionnaire. The subjects of the study were students of class VII Junior High School 14 Pekanbaru, amounting to 41 people and divided into 2 experimental groups and 2 control groups. Determination of sample by using technique of Pusposive Sampling. Data analysis was performed using percentage technique, wilcoxon comparison, mann whiteney different test and rank spearman correlation. Where researchers chose class VII students because of the results of the phenomenon in the field. The result of data analysis showed that the value of Sig. (2-tailed) of 0.063 in group 1 and 0.024 in group 2 with a significance value of 0.05. Sig. (2-tailed)> 0.05 so that Ho is accepted and Ha is rejected in group 1 and Ha is accepted and Ho is rejected in group 2. There is no significant correlation between group guidance to academic procrastination level in group 1 of 33.2% A significant relationship between group guidance on the level of academic procrastination in group 2 was 49.1%. This is evidenced by the correlation value of 0.577 and 0.701 so that the value of the correlation coefficient of group 1 at the level of moderate and group 2 at a strong level. There is a positive relationship between group guidance and the level of student academic procrastinationKey Word: Group guiding, procrastination, academic